Fauré and French musical aesthetics - Caballero, Carlo (Music in the twentieth century., 2001)
This wide-ranging study of Gabriel Fauré and his contemporaries reclaims aesthetic categories crucial to French musical life in the early twentieth century. Its interrelated chapters treat the topics of sincerity, originality, novelty, self-renewal, homogeneity and religious belief in relation to Fauré's music and ideas. Taking a broad view of cultural life during the composer's lifetime and beyond, the book moves between specific details in Fauré's music and related critical, literary and philosophical issues, ranging from Gounod to Boulez and from Proust to Valéry. Above all, the book connects abstract values to artistic choices and thus places such works as Fauré's Requiem, La bonne chanson, La chanson d'Eve, L'horizon chime;rique, and the chamber music in a new light.--Publisher description.